Differential tolerance of a cancer and a non-cancer cell line to amino acid deprivation : mechanistic insight and clinical potential - Thomas, Mark Peter (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2012.